(untitled) (Homiletic, 2011)
The methodological focus of homiletic theories that move from text to sermon has sometimes occluded theological commitments that lurk behind those methods. Rather than viewing contemporary homiletic theory as lacking theological concern, this essay follows Susan Bond’s insight in Contemporary African American Preaching to expose theological commitments behind methodological choices. The article uses in particular M. H. Abram’s typology of literary theories in The Mirror and the Lamp to identify implicit hermeneutical orientations behind both critical approaches to texts (Biblical methods) and what homileticians aim to do in sermons (homiletic theory). The article then construes for preachers Abram’s fourfold typology of literary theories as the world behind the text, the mind of the text, the world of the text, and the audience in front of the text and connects them to four of Avery Dulles’ "models of revelation": revelation as history, inner-experience, dialectical presence, and new awareness. In the process, Jacobsen opens the possibility of thinking about the relationship of homiletic theory to theology in more fruitful and dynamic ways.